2016
DOI: 10.1080/2162402x.2016.1168549
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial NF-κB signaling promotes EGFR-driven lung carcinogenesis via macrophage recruitment

Abstract: Several studies have demonstrated that NF-kB activation is common in lung cancer; however, the mechanistic links between NF-kB signaling and tumorigenesis remain to be fully elucidated. We investigated the function of NF-kB signaling in epidermal growth factor receptor (EGFR)-mutant lung tumors using a transgenic mouse model with doxycycline (dox)-inducible expression of oncogenic EGFR in the lung epithelium with or without a dominant inhibitor of NF-kB signaling. NF-kB inhibition resulted in a significant red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…This pathway is also triggered by ligand-gated receptor binding on the cell surface. The receptors involved include epidermal growth factor receptor (EGFR) (Saxon et al, 2016) toll-like receptor (TLR) (Sun et al, 2017) and tumor necrosis factor receptor (TNFR) (Lee et al, 2017). Activation of these receptors leads to receptor phosphorylation through IKK complex and transcription of the relevant genes.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway is also triggered by ligand-gated receptor binding on the cell surface. The receptors involved include epidermal growth factor receptor (EGFR) (Saxon et al, 2016) toll-like receptor (TLR) (Sun et al, 2017) and tumor necrosis factor receptor (TNFR) (Lee et al, 2017). Activation of these receptors leads to receptor phosphorylation through IKK complex and transcription of the relevant genes.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have reported that the tumor microenvironment (TME) [31][32][33][34][35][36], tumor immunogenicity [37][38][39], tumor-specific mutations, copy number variants [40,41] and abundances of specific intestinal bacteria can [42] affect the efficacy of ICIs. Multiple studies have demonstrated that EGFR mutations in NSCLC are more likely to correlate with an immunosuppressive TME [41,[43][44][45][46][47][48], the tumor mutation burden (TMB) [43,49], and expression of PD-L1 [41,[50][51][52][53]. In addition, EGFR-TKIs may modulate the immune response by regulating TME.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, expression of a constitutively active form of IKKβ (which activates canonical NF-κB) in airway epithelium results in a >3-fold increase in lung tumor formation after treatment with chemical carcinogens (Zaynagetdinov et al, 2012). In addition, studies using a variety of methods to block NF-κB signaling in lung epithelium have revealed a requirement for NF-κB signaling in lung cancer models driven by oncogenic forms of Kras and EGFR (Bassères et al, 2010; Meylan et al, 2009; Saxon et al, 2016; Stathopoulos et al, 2007; Xia et al, 2012). While some studies have shown short-term lung tumor regression following NF-κB inhibition (Bassères et al, 2014; Xue et al, 2011), pharmacologic NF-κB inhibition has not shown definitive long-term benefit in lung cancer models.…”
Section: Introductionmentioning
confidence: 99%